2014
DOI: 10.3844/ajabssp.2014.407.419
|View full text |Cite
|
Sign up to set email alerts
|

The Rural Tourism as Development Opportunity or Farms. The Case of Direct Sales in Sicily

Abstract: Tourism has an important role modifying rural communities in their environmental, economic, social and cultural structures, processes and dynamics. In this context rural tourism plays a primary role because it is not the rural product that reaches the consumer in the purchase point, but it is the consumer (tourist) that has to move towards tourist destination to enjoy the product. So, the aim of this study is to analyse how the opportunities created by the rural tourism can represent a vector to promote the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…On average, the number of the household members is of 4 components. As regards the parents' study title, 52% of the fathers and 54,6% of the mothers have a secondary school certification, while 21,3% of the fathers and 19,3% of the mothers have achieved a university degree (Lanfranchi et al, 2014e;Sgroi et al, 2014).…”
Section: Analysis Of the Preference Of Fruit Consumption Among The Stmentioning
confidence: 99%
“…On average, the number of the household members is of 4 components. As regards the parents' study title, 52% of the fathers and 54,6% of the mothers have a secondary school certification, while 21,3% of the fathers and 19,3% of the mothers have achieved a university degree (Lanfranchi et al, 2014e;Sgroi et al, 2014).…”
Section: Analysis Of the Preference Of Fruit Consumption Among The Stmentioning
confidence: 99%
“…Surveys have shown that there was a positive and strong relationship between tourism and economic growth (Cortes-Jimenez and Pulina, 2010;Adnan Hye and Ali Khan, 2013;Tang and Abosedra, 2014;Pablo-Romero and Molina, 2013;Al-Mulali et al, 2014;Bouzahzah and El Menyari, 2013;Jalil et al, 2013). Sgroi et al (2014) shown that rural communities improve economic growth. Tudisca et al (2014) mentioned sustainable industries such as tourism industry increase economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…According to some authors (Santeramo et al, 2012;Sgroi et al, 2014b;2014e;Testa et al, 2014b;Tudisca et al, 2013a;2013b;2013c;Everard and McInnes, 2013) forest landscape is considered an environmental resource that can originate flows when its value is defined by the connection with other values that increase its usefulness. Landscape, that represent geographical space modelled by man, culture, tradition and human capital represent resources on which PES can be applied.…”
Section: Methodsmentioning
confidence: 99%